2020
DOI: 10.1002/er.5370
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic copyrolysis of metal impregnated biomass and plastic with Ni‐based HZSM‐5 catalyst: Synergistic effects, kinetics and product distribution

Abstract: The present work aims to investigate the thermal behavior, kinetics, thermodynamics, and product distribution during copyrolysis of transition metal salt (Ni, Co, Zn, Cu, and Fe)-added biomass and model compounds with low density polyethylene(LDPE) over a Ni-based HZSM-5 catalyst by TGA and fixed bed reactor. The interactions and reaction mechanisms during copyrolysis were evaluated. The influence of Ni-impregnated biomass (C-M) and Nimodified HZSM-5 (Ni/HZ) on the formation of pyrolysis bio-oil from biomass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Pyrolysis of metal impregnated biomass is another technique that has attracted a lot of attention. 19 The catalyst is quite close to the structure of lignocellulosic in this case and is expected to have a direct effect on principal reactions. 20 The use of ex situ catalysts leads to a decrease in liquid production and an increase in gas yield through the cracking of organic molecules.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Pyrolysis of metal impregnated biomass is another technique that has attracted a lot of attention. 19 The catalyst is quite close to the structure of lignocellulosic in this case and is expected to have a direct effect on principal reactions. 20 The use of ex situ catalysts leads to a decrease in liquid production and an increase in gas yield through the cracking of organic molecules.…”
Section: Introductionmentioning
confidence: 87%
“…In fluidized‐bed reactors, catalysts can also be utilized as bed material. Pyrolysis of metal impregnated biomass is another technique that has attracted a lot of attention 19 . The catalyst is quite close to the structure of lignocellulosic in this case and is expected to have a direct effect on principal reactions 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] CFP of biomass was proved with high efficiency for the preparation of aromatics. [8][9][10][11][12][13][14] Such pyrolysis reactions are usually executed over ZSM-5 zeolite catalysts during CFP of biomass. [15][16][17][18][19][20][21] For example, Bakar et al reported that ZSM-5 could increase the production of aromatics and light phenols during catalytic pyrolysis of rice husk into bio-oil production.…”
Section: Introductionmentioning
confidence: 99%
“…CFP of biomass was proved with high efficiency for the preparation of aromatics 8‐14 . Such pyrolysis reactions are usually executed over ZSM‐5 zeolite catalysts during CFP of biomass 15‐21 .…”
Section: Introductionmentioning
confidence: 99%